Factors shaping regionalism in the Middle East and North Africa: a classical approach - Bendebka, Ramzi (Academia.edu, 2021)
Traditional politics or classical theories and methodologies have profoundly affected international relations approaches to the study of cooperation in the MENA region. This is evident in the writings and contributions of different experts and authors limiting and identifying regionalism in the Middle East as a challenging issue based only on religious and security considerations. Even everyday life in this region is stereotyped as continuing wars. The Middle East and North Africa (MENA) has long been seen as an area that best matches a realistic perspective of international politics (Hinnebusch & Ehteshami, 2002). To begin with, collective political organizations have largely taken the form of regional hegemonies, with collaboration barely progressing beyond the rhetorical stage. Although the idea of Arab unification encourages all Arabs to some extent, the striking contrast between this ideal and the negative consequences of numerous superficial efforts in that direction remains a distinct Arab trait.